Dekadensi Kepemimpinan dan Kritik Profetik dalam Hosea 7: Metafora, Disorientasi Politik, dan Krisis Perjanjian - Ricko Tri Choryntus; Anon Dwi Saputro (Student Evangelical Journal Aiming At Theological Interpretation, 2025)
This article re-examines Hosea 7 as a sustained prophetic critique of Israel’s political and spiritual leadership during the eighth century BCE. While previous scholarship has tended to treat Hosea 7 primarily as a collection of poetic metaphors or moral denunciations, this study argues that the chapter functions as a coherent theological discourse exposing systemic leadership failure rooted in covenantal infidelity. Employing a metaphorical-theological approach integrated with historical and literary analysis, this research demonstrates that the metaphors of the oven, the unturned cake, the gray hair, the foolish dove, and the deceitful bow collectively construct a multidimensional critique of moral decay, political opportunism, and spiritual disorientation among Israel’s leaders. The findings highlight that leadership collapse in Hosea 7 is fundamentally theological rather than merely political, arising from the loss of prophetic ethics and loyalty to YHWH. By extending this prophetic critique to contemporary Christian leadership, the study contributes to biblical leadership studies by proposing a theologically grounded evaluative framework that emphasizes covenantal integrity, prophetic accountability, and God-centered authority as essential markers of faithful leadership.